Morbidity Pattern in Textile Weavers of Urban Belgaum: A Community Based Cross Sectional Study - A.S. Wantamutte, N.D. Zingade, M.D. Mallapur, M.S. Shivaswamy, Deepti M. Kadeangadi*, (Recent Research in Science and Technology, 2010)
Objective: To study the morbidity pattern in adult textile weavers. Study Design: Community-based cross sectional study Period of the study: one year (November 2004 to October 2005) Study participants: 377 adult textile weavers residing in Khasbag, Belgaum Setting: Khasbag urban field practice area of J. N. Medical College, Belgaum Analysis: Frequency distribution in EXCEL 2000 Software Results: The most common morbidities found were noise induced hearing loss (NIHL) - 125 (33.2%), followed by dental stains – 109 (28.9%), hypertension 81 (21.5%), acid peptic disorders - 75 (19.9%), sleep disorders - 69 (18.3%), dental caries - 67 (17.8%), backache - 63 (16.7%), myalgia / fatigue - 60 (15.9%), URTI - 58 (15.4%) and anemia -35 (9.3%). Keywords: Textile weavers, Morbidity, Noise induced hearing loss